Neuronal precursor cells with dopaminergic commitment in the rostral migratory stream of the mouse - Schweyer, Kerstin (Sci Rep, 2019)
Neuroblasts born in the subventricular zone of adult mammals migrate via the rostral migratory stream into the granular cell layer or periglomerular layer of the olfactory bulb to differentiate into interneurons. To analyze if new neurons in the granular cell layer or periglomerular layer have different origins, we inserted a physical barrier into the rostral migratory stream, depleted cell proliferation with cytarabine infusions, labeled newborn cells with bromodeoxyuridine, and sacrificed mice after short-term (0, 2, or 14 days) or long-term (55 or 105 days) intervals. After short-term survival, the subventricular zone and rostral migratory stream rapidly repopulated with bromodeoxyuridine(+) cells after cytarabine-induced depletion. Nestin, glial fibrillary acidic protein and the PAX6 were expressed in bromodeoxyuridine(+) cells within the rostral migratory stream downstream of the physical barrier. After long-term survival after physical barrier implantation, bromodeoxyuridine(+) neurons were significantly reduced in the granular cell layer, but bromodeoxyuridine(+) and dopaminergic neurons in the periglomerular layer remained unaffected by the physical barrier. Thus, newborn neurons for the granular cell layer are mainly recruited from neural stem cells located in the subventricular zone, but new neurons for the periglomerular layer with dopaminergic predisposition can rise as well from neuronal stem or precursor cells in the rostral migratory stream.